Proceedings of the 2000 Academy of Marketing Science (AMS) Annual Conference - Spotts, Harlan E.; Meadow, H. Lee.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Founded in 1971, the Academy of Marketing Science is an international organization dedicated to promoting timely explorations of phenomena related to the science of marketing in theory, research, and practice. Among its services to members and the community at large, the Academy offers conferences, congresses and symposia that attract delegates from around the world. Presentations from these events are published in this Proceedings series, which offers a comprehensive archive of volumes reflecting the evolution of the field. Volumes deliver cutting-edge research and insights, complimenting the Academy$1 (Bs flagship journals, the Journal of the Academy of Marketing Science (JAMS) and AMS Review. Volumes are edited by leading scholars and practitioners across a wide range of subject areas in marketing science. This volume includes the full proceedings from the 2000 Academy of Marketing Science (AMS) Annual Conference held in Montreal, Canada.s
Buyer Behavior in International Markets -- Advertising and Consumer Behavior -- Customer Delivery Systems: From Mom and Pop to the WWW -- Managing Marketing Relationships Within and Across Firms -- Globalization: A Marketing Management Perspective -- The Active Service Consumer -- Service on the Edge -- The Outcome of Value Creation: Satisfaction & Patronage -- Satisfaction, Patronage, and Profitability: Is There a Retailing Relationship? -- Adding Value to Marketing Through Integration -- Vulnerable and At-Risk Consumers -- Teaching Philosophies of Outstanding Teachers -- Integration: Where Does Marketing Fit? -- The Role of Information in Global Marketing -- Buyer Characteristics -- Marketing Alliances between Businesses and Nonprofits -- Globalization: Culture and Values -- Trends and Practices in the Government Environment -- Industrial Communications -- Understanding Evaluations in Ethical Decision Making -- Entrepreneurship, Innovation and Performance in Established Firms -- Globalization: Culture and the Media -- Marketing, Effectiveness, and the Integrated Curriculum -- Choice Models and Multivariate Methods -- Is Good Citizenship Good Business? Cognitive and Affective Dimensions of Buyer Behavior -- Electronic Commerce, Quality, and Public Policy -- Ethical Attitudes and Behaviors in Marketing Practices -- Marketing Across Cultures -- The Product and Price Components of Value -- Topic Tables: Marketing in the Millennium -- Marketing Mix Decisions in the Global Context -- Country Risks and Marketing Practices in the Global Context -- Measurement Issues in Service Marketing -- Building, Evaluating, and Benefiting from Corporate Citizenship and Codes of Ethics -- Entrepreneurship as it Relates to Networks, Alliances and Alternative Contexts -- Strategic Marketing Management -- Marketing Tools in Not-For-Profit Settings -- Latent Variable Interactions and IRT -- Country Risks and Marketing Practices in the Global Context (continued) -- Discussant Comments.
Keywords: Economics; Marketing; Economics/Management Science; Marketing; Business Strategy/Leadership.; Sales/Distribution/Call Center/Customer Service